Impact of Dietary Nutmeg (Myristica fragrans) Powder Supplementation on Hematological and Biochemical Parameters of Ross 308 Broiler Chickens - Abdullah, Mariya M.; Salih, Hayfaa Mohammed (American Journal of Biodiversity, 2026)
This research was carried out at the Animal Production Field, College of Med. & Ind. Plants, Uni. of Kirkuk, between March 17 and April 20, 2024, to assess the impact of dietary nutmeg powder supplementation on specific blood parameters of Ross 308 broilers. Birds were randomly assigned to four treatments: T1 (control), T2 (1 g/kg), T3 (2 g/kg), and T4 (3 g/kg) diets. There was no significant difference (P > 0.05) for the hematological parameters, where the highest number of red blood cells was recorded for the control group (12.01×106/mm3), the highest value of hemoglobin was recorded for T4 (11.17 g dL-1), and the highest packed cell volume was recorded for T2 (29.25%). This indicated that the diet supplemented with up to 3 g/kg of nutmeg powder did not adversely affect the blood health status of the birds. Conversely, significant differences (P<0.05) were observed in the biochemical parameters, where total cholesterol decreased from 108.3 mg dL-1 in the control treatment to 84.63 mg dL-1 in T4, triglycerides declined from 129.74 to 89.74 mg dL-1, LDL decreased from 57.73 to 30.99 mg dL-1, and VLDL decreased from 25.94 to 17.94 mg dL-1, while HDL increased from 47.70 mg dL-1 in the control to 59.54 mg dL-1 in T4. The improvement was more pronounced at the 2 and 3 g/kg inclusion levels, suggesting that nutmeg powder can be used as a safe and effective phytogenic feed additive to improve serum lipid profile without affecting hematological stability under the conditions of this study.